A Novel Bivalent Mannosylated Targeting Ligand Displayed on Nanoparticles Selectively Targets Anti-Inflammatory M2 Macrophages - Peiming Chen; Xiaoping Zhang; Alessandro Venosa; In Heon Lee; Daniel Myers; Jennifer A. Holloway; Robert K. Prud'homme; Dayuan Gao; Zoltan Szekely; Jeffery D. Laskin; Debra L. Laskin; Patrick J. Sinko (MDPI AG, 2020)
Persistent activation of macrophages (MP)s into a proinflammatory M1 or anti-inflammatory M2 phenotype plays a role in several pathological conditions, including autoimmune diseases, fibrosis, infections, atherosclerosis and tumor development. The mannose receptor (MR, CD206), expressed at low levels on resting MPs and absent on M1 MPs, is highly expressed on M2 MPs, making it a potential target and drug delivery portal. Recently, we developed a novel, highly selective MR targeting ligand (MRTL), consisting of two mannose molecules separated by a monodisperse 12 unit poly(ethylene glycol) linker, to enhance the cellular uptake of polymeric nanocarriers. The feasibility of using the MRTL ligand for selectively targeting M2 MPs for intracellular delivery of nanoparticles (NPs) was investigated. Rat peritoneal MPs were differentiated into an M1 or M2 phenotype using IFN-γ and IL-4/IL-13, respectively. Expression of the M1 marker, inducible nitric oxide synthase (iNOS), and the M2 markers arginase (Arg)-1 and MR (at both the mRNA and protein levels) confirmed MP phenotypic activation. Resting, M1 and M2 MPs were treated with fluorescein isothiocyanate (FITC)-labeled MRTL or NPs displaying FITC-labeled MRTL at two surface densities (1 and 10%) and examined by confocal microscopy. Intracellular fluorescence was also quantified. Uptake of the MRTL was 2.4- and 11.8-fold higher in M2 MPs when compared to resting or M1 MPs, respectively, consistent with marker expression levels. Mannan, a competitive inhibitor of the MR, abrogated MRTL uptake. MRTL also co-localized with a fluid-phase endocytosis marker, further suggesting that uptake was mediated by MR-mediated endocytosis. Intracellular NP fluorescence was confirmed by flow cytometry and by confocal microscopy. MRTL-NPs accumulated intracellularly with no significant cell surface binding, suggesting efficient translocation. NPs displaying a low surface density (1%) of the MRTL exhibited significantly higher (2.3-fold) uptake into M2 MPs, relative to resting and M1 MPs. The 10% MRTL-NPs displayed greater uptake by M2 MPs when compared to resting and M1 MPs, but less uptake than 1% MRTL-NPs into M2 MPs. Control FITC-labeled plain NPs did not exhibit selective MP uptake. These studies demonstrate that M2 MPs are selectively targeted by NPs displaying a novel bivalent ligand that utilizes the MR as a target/portal for cell entry. This study also establishes the feasibility of the approach allowing for further investigation in vivo.